Community participation cum socio-economic development; in the 21st-century Somopho community. Kwazulu-Natal, South Africa - Adetiba, Toyin (Technium Social Sciences Journal, 2021)
Community development to a large extent is a dynamic process that involves the cooperation of both the members of a particular community, NGOs, and government agencies. Over a long period, there has been a steadier process of economic and social change in rural communities through their steady participation commonly understood as their collective involvement in assessing their needs and organizing strategies to meet those needs. Using a mixed-methods approach this work argued that as part of community development, it is believed that citizen’s participation is necessary because it results in better decisions when community members are involved in decision-making vis-à-vis project implementation while seeking a lasting change for individuals and the communities and societies in which they live. The work concludes that when the objective of community development is empowerment and capacity building, sustainable socio-economic and cultural development, the community will not be far from achieving its goals of sustaining and accelerating community members’ participation in their development.